The influence of diabetes on degree of abdominal aortic aneurysm tissue inflammation - Arapoglou, V.; Kondi-Pafiti, A.; Rizos, D.; Carvounis, E.; Frangou-Plemenou, M.; Kotsis, T.; Katsenis, K. (Vascular and Endovascular Surgery, 2010)
Abdominal aortic aneurysm (AAA) progression and disease resistance are related to transmural degenerative processes and an inflammatory infiltration (INF). Diabetes is associated with low prevalence and growth rate of AAA. We sought to characterize INF in established AAA (INFAAA), in diabetic patients. From 89 male patients aged 52 to 83 years, aneurysm specimens obtained at open asymptomatic nonruptured AAA repair were graded for INF and immunostained using antibodies against T-lymphocytes (CD3) and macrophages (CD68). Diabetic patients had an odds ratio (OR) 3.8, 95% confidence interval ([CI] 1.14-12.96), P =.03, of experiencing above-median INFAAA. These associations were affected by serum glucose (SG) levels (OR 3.6, 95% CI [0.72-18.77]; P =.1). Macrophage subpopulations higher in diabetic patients (1.44 ± 0.78 versus 0.98 ± 0.76; P =.02) were correlated with SG (r =.21, P =.044). Abdominal aortic aneurysms in diabetic patients are associated with higher INF. Macrophage densities are correlated with SG. © The Author(s) 2010.
Keywords: Abdominal aortic aneurysm; diabetes; Inflammation